Violência de gênero e crime passional: um estudo do caso Nirvana - SILVA, Fernando César Louzada e (Universidade Federal do Pará, 2017)
The present dissertation studies the solution given by the Brazilian Judiciary System concerning to gender conflict which is in the core of judgements of passional crimes when the victims are women. As empirical analysis it was chosen the Nirvana Case, in order to analyse gender conflict in Belém. This analysis begins with the concept of truth, and related difficulties for its apprehension because there are models of behavior for gender’s roles, as well as the framing procedures whether in the Police Stations or in the Courts. Essential categories are established for the understanding of the issue, such as the concepts of emotion and passion; passional crime; basic notions of Criminal Law and Criminal Law Process. It also aims to evaluate, in the vigency of the Law 11.340, called Maria da Penha Law, the repercussions of androcentrism on decisions of Grand Jury, which are made through discriminatory discourses and through attorney’s defense strategies in Court, which reborn the legitimate defense of honor. From this analysis, it will be proposed solutions in order to give adequate responses against this kind of decision, and according to the current status of the Human Rights and the Democratic State of Law.